Global challenges of digital transformation of markets - De la Poza, Elena; Barykin, Sergey E. (Economic Issues, Problems and Perspectives Ser., 2021)
"As rapid changes are brought on by technologies and by the challenges facing humanity, existing businesses consistently update and reinvent. This book tackles the challenges of adopting and reinventing business models due to the digital transformation in logistics and supply chain management, digitization of trade networks and global markets, with a primary focus on business processes, marketing transformation and human resources management"--